ANFIS -based navigation for HVAC service robot with image processing - Salleh, Mohd Zoolfadli Md; Alang Md Rashid, Nahrul Khair; Mohd Mustafah, Yasir (IOP Publishing, 2013)
In this paper, we present an ongoing work on the autonomous navigation of a mobile service robot for Heat, Ventilation and Air Condition (HVAC) ducting. CCD camera mounted on the front-end of our robot is used to analyze the ducts openings (blob analysis) in order to differentiate them from other landmarks (blower fan, air outlets and etc). Distance between the robot and duct openings is measured using ultrasonic sensor. Controller chosen is ANFIS where its architecture accepts three inputs; recognition of duct openings, robot positions and distance while the outputs is maneuver direction (left or right).45 membership functions are created from which produces 46 training epochs. In order to demonstrate the functionality of the system, a working prototype is developed and tested inside HVAC ducting in ROBOCON Lab, IIUM.